Creative economy: support of creative hubs by the public sector in the urban environment - Chaloupková, Markéta; Kunc, Josef; Koutský, Jaroslav (Technological and Economic Development of Economy, 2023)
Creative hubs are institutional organization of newly emerging creative industries. Economic activities associated with creative industries are very often business-oriented and strongly independent. However, there are often needs for public sector. The aim of paper is to analyze the situation in the Czech Republic and assess the involvement and benefits of the public sector towards the support of these business activities. Methodologically, the work is based on several approaches. Primarily, a database of Czech creative hubs was created as part of desk research. This was followed by quantitative questionnaire survey with representatives of creative hubs and qualitative research in the form of structured interviews with representatives of hubs and the public sector. It was found that without public finances and interest, Czech creative hubs cannot function in the long term. Financial support is therefore the most common form of public support. The main strength of hubs lies in the built community of members, offered services and networking. Conversely, the main weakness is the inability to secure sufficient funds and sponsors. Although public sector cooperation in the Czech Republic is still limited, many public representatives are beginning to realize the benefits of the creative economy and gradually implement it into policies.